D7‐brane moduli space in axion monodromy and fluxbrane inflation. Issue 8 (14th July 2014) - Arends, M.; Hebecker, A.; Heimpel, K.; Kraus, S.; Lüst, D.; Mayrhofer, C.; Schick, C.; Weigand, T.
Abstract We analyze the quantum‐corrected moduli space of D7‐brane position moduli with special emphasis on inflationary model building. D7‐brane deformation moduli are key players in two recently proposed inflationary scenarios: The first, D7‐brane chaotic inflation, is a variant of axion monodromy inflation which allows for an effective 4d supergravity description. The second, fluxbrane inflation, is a stringy version of D‐term hybrid inflation. Both proposals rely on the fact that D7‐brane coordinates enjoy a shift‐symmetric Kähler potential at large complex structure of the Calabi‐Yau threefold, making them naturally lighter than other fields. This shift symmetry is inherited from the mirror‐dual Type IIA Wilson line on a D6‐brane at large volume. The inflaton mass can be provided by a tree‐level term in the flux superpotential. It induces a monodromy and, if tuned to a sufficiently small value, can give rise to a large‐field model of inflation. Alternatively, by a sensible flux choice one can completely avoid a tree‐level mass term, in which case the inflaton potential is induced via loop corrections. The positive vacuum energy can then be provided by a D‐term, leading to a small‐field model of hybrid natural inflation. In the present paper, we continue to develop a detailed understanding of the D7‐brane moduli space focusing among others on shift‐symmetry‐preserving flux choices, flux‐induced superpotential in Type IIB/F‐theory language, and loop corrections. While the inflationary applications represent our main physics motivation, we expect that some of our findings will be useful for other phenomenological issues involving 7‐branes in Type IIB/F‐theory constructions.